2023
DOI: 10.3389/fpls.2023.1144461
|View full text |Cite
|
Sign up to set email alerts
|

The optimum economic nitrogen rate of blended controlled-release nitrogen fertilizer for rice in the Chanoyu watershed in the Yangtze River Delta, China

Abstract: IntroductionThe application of controlled-release nitrogen fertilizer (CRN) has become an important production method to achieve high crop yield and ecological safety. However, the rate of urea-blended CRN for rice is usually determined by conventional urea, and the actual rate is still unclear.MethodsA five-year field experiment was carried out in the Chaohu watershed in the Yangtze River Delta to study rice yield, N fertilizer utilization efficiency (NUE), ammonia (NH3) volatilization and economic benefit un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Two CRNs with the N release periods of 40 and 90 days are abbreviated as CRN1 and CRN2, respectively. The N release characteristics of CRN1 and CRN2 in 25°C water and paddy fields for 42 and 100 days were measured in the 2019 ( Yuan et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two CRNs with the N release periods of 40 and 90 days are abbreviated as CRN1 and CRN2, respectively. The N release characteristics of CRN1 and CRN2 in 25°C water and paddy fields for 42 and 100 days were measured in the 2019 ( Yuan et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that the average rice N-use efficiency (NUE) is only 39% ( Yu and Shi, 2015 ), which is 33.3-42.9% lower than that of the United States of America and Europe ( Lassaletta et al., 2014 ; Yu et al., 2022 ). Excessive application of N fertilizer not only increases the production cost of rice, but also reduces NUE, and causes environmental problems such as soil acidification and water eutrophication ( Congreves et al., 2021 ; Yuan et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations